2015
DOI: 10.3889/oamjms.2015.101
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on BMI, Serum Testosterone and Estradiol Levels in Allergic Male Patients

Abstract: BACKGROUND:The dramatic increase in the prevalence of high body mass index (BMI) increases the prevalence of allergic diseases, both in adults and children and obesity is associated with hypogonadism in adult males.AIM:We aimed to evaluate the effect of high body mass index on plasma concentrations of testosterone and estradiol in young pubertal and adult males with allergic diseases.MATERIAL AND METHODS:Morning fasting blood samples were obtained form 51 allergic patients and 6 healthy volunteer males between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…8,10,11 In the only study reported in the literature to investigate ED and the testosterone levels in male patients with allergic, it was shown that the testosterone level was lower in patients with asthma compared with the healthy control group, but there were no significant differences between two groups. 29 Similarly, in the current study, we detected that the testosterone level was lower in asthma patients compared with the control group, and differences between groups were significantly. Although the testosterone level in asthmatic patients is lower than the control group, the concentration of testosterone in our asthmatics (Mean ± SD:…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…8,10,11 In the only study reported in the literature to investigate ED and the testosterone levels in male patients with allergic, it was shown that the testosterone level was lower in patients with asthma compared with the healthy control group, but there were no significant differences between two groups. 29 Similarly, in the current study, we detected that the testosterone level was lower in asthma patients compared with the control group, and differences between groups were significantly. Although the testosterone level in asthmatic patients is lower than the control group, the concentration of testosterone in our asthmatics (Mean ± SD:…”
Section: Discussionsupporting
confidence: 75%
“…In a few studies, it was reported that testosterone may be low in respiratory diseases such as COPD 8,10,11 . In the only study reported in the literature to investigate ED and the testosterone levels in male patients with allergic, it was shown that the testosterone level was lower in patients with asthma compared with the healthy control group, but there were no significant differences between two groups 29 . Similarly, in the current study, we detected that the testosterone level was lower in asthma patients compared with the control group, and differences between groups were significantly.…”
Section: Discussionmentioning
confidence: 96%
“…Although obesity has been associated with increased IgE responses and allergic symptoms, whether it predisposes to an increased food allergy risk remains to be tested. [48][49][50][51] To investigate whether HFD feeding confers an increased risk of food allergy, wild-type C57BL/6J mice were fed an HFD (45 kcal% fat, D12451i; Research Diets), a matching control diet (10 kcal% fat, D12450H; Research Diets), or an SCD (4.5 kcal% fat; Provimim Kliba SA) for 12 weeks before induction of experimental food allergy (Fig 1, A). After establishment of obesity in the HFD group (Fig 1, B-D, and see Fig E1 in this article's Online Repository at www.jacionline.…”
Section: High Dietary Fat Intake Potentiates Food-induced Allergic Rementioning
confidence: 99%
“…Generally, testosterone has been considered to act as immunosuppressant, and earlier studies have found low testosterone levels in atopic diseases patients, including atopic dermatitis [ 24 ], asthma alone and asthma with allergic rhinitis [ 25 ]. These studies support low levels of testosterone may be associated with the presence of atopic diseases.…”
Section: Discussionmentioning
confidence: 99%